MAGICAL REALISM IN ANDREA CREMER AND DAVID LEVITHAN’S NOVEL INVISIBILITY - Nisa Asha Syahputra; Mamik Tri Wedawati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Andrea Cremer and David Levithan’s Invisibility is a contemporary novel with a twist of magical realism. Stephen and Elizabeth, the main characters, had made the story in the novel different colors. The study focused on how magical realism was presented in the novel through its five characteristics: irreducible element, the phenomenal world, unsettling doubts, merging realms, and disruptions of time, space, and identity. Applying Wendy B. Faris’ perspective, this study examined extraordinary things that happened within the ordinary to sort them into said characteristics of magical realism. The qualitative research method applied proved that in Cremer and Levithan’s Invisibility, there existed extraordinary events for each magical realism element, such as Stephen’s abrupt disappearance when Elizabeth blinked as the irreducible element; Stephen’s acceptance of being invisible and living in a accessible place like New York as the phenomenal world; Elizabeth’s doubts concerning Stephen’s form as the unsettling doubt; an ordinary-looking comic store being a magical office in disguise as the merging realm; and Elizabeth’s ability to enter into a different side of the regular universe as the disruption of space.